Board Diversity and Sustainability Reporting: Empirical Evidence from Indonesian Listed Banks - Prihatnolo Gandhi, Amidjaya; Josephine, Yau Tan Hwang; Sharon Cheuk, Choy Sheung (Human Resource Management Academic Research Society (HRMARS), 2023)
Sustainability reporting has gained a significant attention due to its importance for sustainable development goals. Following the increased concern of sustainability reporting in Indonesian business, this study examines the effect of board of commissioner’s diversity on sustainability reporting in Indonesian listed banks. The study explores the topics by following the concept of agency theory. Our study employs secondary data obtained from the annual and sustainability reports from 2014-2018. By using purposive sampling method, the study generates 210 observations in which the analysis is conducted with panel data regression using STATA statistics software. Our study finds that the sustainability reporting implementation of by Indonesian listed banks is still considerably low. There is also no significant improvement since the release of roadmap for sustainable finance in 2014 that enforce sustainability reporting for banking sector. Panel data regression analysis reveals that board’s gender diversity exhibits positive effect on sustainability reporting. Meanwhile, board’s diversity in nationality, age, and education have no significant effect on sustainability reporting practice. The insignificant effect may be due to the fact that the board is still dominated by of local board members, older board members, and board members with business education background. Based on our findings, we suggest the Indonesia Financial Service Authority (OJK) as the capital market regulator to improve firms' understanding about sustainability reporting and apply higher enforcement of its implementation. The OJK can optimize the role of board diversity as it has not contributed significantly to improving sustainability reporting practice. Further, future studies can be improved by employing mixed method by combining quantitative and qualitative analyses and also extending the coverage of the study.